EXAMINING THE INTERPLAY OF NUMERICAL MAPPING ABILITIES, MATHEMATICS ACHIEVEMENT, AND SOCIOECONOMIC STATUS IN 4- AND 5-YEAR-OLD CHILDREN (International Journal of Food and Nutritional Sciences, 2021)
Success in school and in life depends on having strong numeracy abilities from a young age. Math scores are lower for children from low-income families, and this disadvantage may exist even before they start school. It would be possible to enhance life chances and scaffold math learning by understanding the link between the abilities that assist the development of early arithmetic skills. The purpose of this research was to compare the mathematical performance of students from diverse socioeconomic backgrounds on a task that required them to convert between symbolic (arabic numerals) and nonsymbolic (dot arrays) representations of numbers at two distinct levels of difficulty. Participating children were 398 in their first year of elementary school (mean age= 60 months), with 75% hailing from low-income families.